Overcoming resistance to immunotherapy by teaching old drugs new tricks. (2nd September 2020) - Perry, John M.; Li, Linheng
ABSTRACT: Cancer stem cells (CSCs) underlie resistance to therapy. Cancer develops only in the context of failing immunosurveillance, and stem cells occupy immune privileged microenvironments. Recent evidence demonstrates that CSCs borrow immune privilege from their normal counterparts. However, low doses of doxorubicin can target CSCs by restoring anticancer immunity.